2007
DOI: 10.1038/sj.sc.3102054
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of natural killer cell activity during 2-h exercise in individuals with spinal cord injuries

Abstract: Design: Non-randomized study. Objective: To determine natural killer cell cytotoxic activity (NKCA) to 2-h arm ergometer exercise in persons with spinal cord injuries (SCI) and the underlying mechanism of such response. Setting: University of Occupational and Environmental Health, Japan. Methods: We examined NKCA response to 2-h arm crank ergometer exercise at 60% of maximum oxygen consumption (VO 2max ) in SCI and able-bodied persons. NKCA and plasma concentrations of prostaglandin E 2 (PGE 2 ), adrenaline an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 19 publications
1
17
0
Order By: Relevance
“…10 NKCA increased significantly in AB immediately after exercise, but decreased significantly in SCI immediately after exercise. 10 Cortisol levels remained constant throughout the experiment in all subjects. In this study, with substantially shorter exercise duration, NKCA in CSCI did not decrease immediately after exercise.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…10 NKCA increased significantly in AB immediately after exercise, but decreased significantly in SCI immediately after exercise. 10 Cortisol levels remained constant throughout the experiment in all subjects. In this study, with substantially shorter exercise duration, NKCA in CSCI did not decrease immediately after exercise.…”
Section: Discussionmentioning
confidence: 84%
“…for 3 min before the supernatant was removed, and cells were then resuspended in 250 ml 1% Other blood tests Total blood cell counts, hematocrit, the percentage of neutrophils, total lymphocytes, and monocytes, plasma catecholamines, and cortisol levels were measured using the methods described earlier. 10 Statistical analysis Data were expressed as mean±standard error of the mean (s.e.m.) and analyzed using a 2 Â 4 repeated measures analysis of variance (ANOVA).…”
Section: Study Protocolmentioning
confidence: 99%
See 1 more Smart Citation
“…More strenuous and prolonged upper-body exercise (>60 min) has been shown to significantly decrease the number of NK cells and their cytotoxicity postexercise [19], but this compromised response did not occur in nondisabled athletes [20]. It was proposed that these differences were likely mediated by changes in cortisol [19] and prostaglandin E2 in the SCI group [20].…”
Section: Introductionmentioning
confidence: 99%
“…Previously, studies have reported increases in circulating NK cell number and cytotoxicity (part of innate immunity) in sedentary SCI individuals following electrically stimulated cycling [17] and 20 min of orthotic gait exercise [18]. More strenuous and prolonged upper-body exercise (>60 min) has been shown to significantly decrease the number of NK cells and their cytotoxicity postexercise [19], but this compromised response did not occur in nondisabled athletes [20]. It was proposed that these differences were likely mediated by changes in cortisol [19] and prostaglandin E2 in the SCI group [20].…”
Section: Introductionmentioning
confidence: 99%